(untitled) (Journal Of Educational and Psychological Researches, 2023)
The study is concerned with the problem of the earthly identity of kindergarten children by verifying its aims in identifying the earthly identity of the first level of kindergarten children and the earthly identity of both levels of the kindergarten. The research also aims to identify the earthly identity of male and female kindergarten children. The study population is represented in public and private kindergartens on both sides of Baghdad city, Karkh & Rusafa for the academic year (2022-2023). The earthly identity test in its final form consisted of (10) items. The test was administered to a sample of (400) children in public and private kindergartens, who were selected randomly. The results showed that kindergarten children have a good earthly identity. There are no significant differences between males and females in earthly identity according to the two levels of kindergarten. The research came out with a number of recommendations and suggestions